STRATA: A Performance-Based Film Project on Deep Time in the Body and the Geologic - Stenke, Verena; Pagnes, Andrea (UnderCurrents: Journal of Critical Environmental Studies, 2025)
This article introduces a poem excerpted from the text of STRATA, VestAndPage’s fifth performance-based film project, which deals with the notion of deep time, the formation of layers in human history, memory, and the geological. The lyrics exemplify how VestAndPage resume through poetic words their thought process, the information gathered during their artistic research that led to the making of the film, and the felt emotions and perceived sensations while performing inside the Swabian Jura caves system, the location in which they chose to produce the film. The authors highlight topics that serve as the framework for their co-creative processes, such as transcendental imagination and queer ecology, in discussing their experience of making the film.